A heparan-like glycosaminoglycan from the white jade snail: Precise structural elucidation, alkaline-induced artificial changes, and non-anticoagulant heparanase inhibition - Pin Wang; Na Gao; Qijiang Mao; Lutan Zhou; Yu Wang; Ying Pan; Fengyun Wu; Penghao Kang; Zanyang Min; Yujun Ma; Huifang Sun; Xiang Shi; et al. (Carbohydrate Polymers, 2026)

Changes in decomposition rates and nutrients of leaf litter and fine roots in urban tree species under ozone pollution - Xiaofan Hou; Pin Li; Yuqian Sun; Chenhan Ma; Jing Fu; Weixia Huang; Zhuoran Zou (Urban Forestry & Urban Greening, 2026)

Heteroatom bridging chemistries enabling fast polysulfide redox and stable lithium deposition - Guangfeng Zeng; Ruiqing Luo; Yumei Qin; Xue Li; Fangting Xie; Jiajia Wang; Shulong Wang; Jingru Liang; Zhiqi Ma; Duming Wei; Qi-Pin Qin; Xiang-Long Huang (Chemical Engineering Journal, 2026)

Multi-target antidiabetic peptides from highland barley (Qingke): Identification, molecular docking, and inhibitory mechanisms against α-amylase, α-glucosidase, and DPP-IV - Juan Li; Muyan Ma; Feng Liang; Yan Du; Wenju Zhou; Pin Ma; Falin Zhang; Zhaoxin Tu; Li Wang; Xinxia Zhang; Ting Li (Food Chemistry, 2026)

Provenance evolution of Late Mesozoic clastic rocks in the Qamdo Basin of eastern Qinghai-Tibet Plateau: Sedimentary response to the Lhasa and Qiangtang terranes collision - Changzhong Li; Weiliang Miao; Xiying Zhang; Xiaochen Ma; Pin Gao; Huanen Gu; Dengxian Zhu (Gondwana Research, 2026)

Consolidation characteristics of diatomaceous soil in coastal reclamations revealed by CPTu tests - Pin-Qiang Mo; Yu-cheng Li; Guojun Cai; Qiuzhu Ma; Hai-Sui Yu (Engineering Geology, 2026)

Site-specific heterogeneity overrides park-type effects in shaping divergent phyllosphere and rhizosphere microbiomes across urban green spaces - Yun Li; Pin Li; Xiaofan Hou; Chenhan Ma; Yushu Tian; Qiannan Lin (Plant and Soil, 2026)

Hydrothermal acid leaching process with ultra-high efficiency for vanadium from spent catalyst - Quanxian Hua; Junyang Ma; Pin Xu; Shu Zhang; Jingjing Rong; Zehao Chen (Minerals Engineering, 2025)

Novel insights into the effect of sTIM-3 on NLRP3 inflammasome via interacting with ASC - Xiaodi Zhang; Na Han; Ziqing Xu; Zheng Tong; Xiaolei Ren; Yang Sun; Chunyang Li; Xuetian Yue; Zhuanchang Wu; Xiaohong Liang; Chunhong Ma; Pin Wang; et al. (Inflammation Research, 2025)

Exploring the mechanism of cinobufagin on gastric cancer based on proteomics, molecular dynamics, in vitro and in vivo experiment - Pin Wang; Xia Zhang; Hanwei Ma; Youcheng Zhang (Toxicology and Applied Pharmacology, 2025)

Effect of layered grinding on the distribution and binding forms of protein and polyphenols in highland barley bran - Muyan Ma; Feng Liang; Wenju Zhou; Pin Ma; Chengjun Ji; Yan Du; Zhaoxin Tu; Li Wang; Xinxia Zhang; Ting Li; Juan Li (Food Bioscience, 2025)

Aging of textile-based microfibers in both air and water environments - Shuyu Ma; Xiaopeng Min; Lin Xu; Xiaolong Jiang; Yanan Liu; Pin Gao; Peng Ji; Hyunjung Kim; Li Cai (Water Research, 2025)

Upregulation of circRNA_0002286 protects against brain ischemia/reperfusion injury after remote ischemic postconditioning via microRNA-124-3p/VLCAD axis - Chun-Yan Li; Wei Ma; Jin-Wei Yang; Wei Liu; Kuang-Pin Liu; Xiao-Hua Weng; Shou-Rui Niu; Shen Li; Jian-Hui Guo; Li-Yan Li (Journal of Molecular Histology, 2025)

Loss of circular EYA3 attenuates formaldehyde-induced cardiomyocyte pyroptosis and congenital heart defects by regulating Smad5 stability - Ying Zhang; Yanyan Yang; Xiangqin He; Pin Sun; Xiaoxia Song; Yu Tian; Jianmin Ma; Ruicong Sun; Tao Yu; Zhirong Jiang (Science of The Total Environment, 2025)

Structure identification and biological activity of a novel sulfated glycosaminoglycan-like polysaccharide from Sepia recurvirostra ink - Nanqi Cheng; Na Gao; Pin Wang; Yujun Ma; Pengfei Li; Xiaolu Wu; Jiaying Sun; Yulan Dai; Jinhua Zhao (Carbohydrate Polymers, 2025)

Sedimentary Signatures of Super Typhoon Haiyan: Insight from Core Record in South China Sea - Yu-Huang Chen; Chih-Chieh Su; Pai-Sen Yu; Ta-Wei Hsu; Sheng-Ting Hsu; Hsing-Chien Juan; Yuan-Pin Chang; Yu-Fang Ma; Shye-Donq Chiu (Journal of Marine Science and Engineering, 2024)
Sedimentary records of event deposits are crucial for regional natural disaster risk assessments and hazard history reconstructions. After Super Typhoon Haiyan passed through the South China Sea in 2013, five gravity cores were collected along the typhoon path in the southern South China Sea basin (>3800 mbsl). The results showed that Super Typhoon Haiyan deposits with clear graded bedding are preserved at the top of all cores. The thickness of the typhoon layers ranges from 20 to 240 cm and is related to changes in typhoon intensity. The lack of river-connected submarine canyon systems limited the transportation of terrestrial sediments from land to sea. Super Typhoon Haiyan-induced large surface waves played an important role in carrying suspended sediment from the Philippines. The Mn-rich layers at the bottom of the typhoon layers may be related to the soil and rock composition of the Palawan region, which experienced tsunami-like storm surges caused by Super Typhoon Haiyan. These Mn-rich layers may serve as a proxy for sediment export from large-scale extreme terrigenous events. This study provides the first sedimentary record of extreme typhoon events in the deep ocean, which may shed light on reconstructing regional hazard history.

The Effect of Platelet Fibrin Plasma (PFP) on Postoperative Refractory Wounds: Physiologically Concentrated Platelet Plasma in Wound Repair - Lu Fan; Ying Zhang; Xiankun Yin; Silu Chen; Pin Wu; Tianru Huyan; Ziyang Wang; Qun Ma; Hua Zhang; Wenhui Wang; Chunyan Gu; Lu Tie; et al. (Tissue Engineering and Regenerative Medicine, 2024)

Emerging transition metal sulfide/MXene composites for the application of electrochemical energy storage - Xianghui Hu; Pin Ma; Zehao Zhang; Jian Wang; Cheng Li; Yee Sin Ang; Haibo Li; Hui Ying Yang (Chemical Engineering Journal, 2024)

Targeted delivery of food functional ingredients in precise nutrition: design strategy and application of nutritional intervention - Xu Wang; Guohua Shi; Sufang Fan; Junmei Ma; Yonghuan Yan; Mengtian Wang; Xiaozhi Tang; Pin Lv; Yan Zhang (Critical Reviews in Food Science and Nutrition, 2024)

Research on the Power Output of Different Floating Wind Farms Considering the Wake Effect - Jiaping Cui; Xianyou Wu; Pin Lyu; Tong Zhao; Quankun Li; Ruixian Ma; Yingming Liu (Journal of Marine Science and Engineering, 2024)
For floating wind turbines, one of the most interesting and challenging issues is that the movement of the rotor is strongly related to its floating platform, which results in corresponding variations in the wake characteristics of the turbine. Because the aerodynamic efficiency of the downstream turbines is affected by the wake characteristics, the power output will consequently vary depending on the different types of floating wind turbines and floating wind farms used. In this study, the rotor movement, wake characteristics, and corresponding wind farm power output are analyzed using a numerical method for three typical floating wind turbines: the semisubmersible type, spar buoy type, and tension leg platform type with a 5 MW configuration. A fixed-bottom monopile wind turbine is adopted as a benchmark. The simulation results show that of the three floating wind turbines, the rotor position and wake center are most dispersed in the case of the spar buoy type, and its wake also has the lowest impact on downstream wind turbines. Additionally, the power output of the corresponding spar buoy type wind farm is also the highest at different wind speeds, followed by the semisubmersible type, tension leg platform type, and then the fixed-bottom type. In particular, at low wind speeds, the wake effects differ significantly among the various types of wind turbines.

1300-m-High gas plume from pockmarks in the north Nansha waters, South China sea - Yanlin Wang; Guanghong Tu; Junhui Yu; Pin Yan; Jinfeng Ma; Zhuangcai Tian; Changliang Chen (Marine and Petroleum Geology, 2024)

Nuclear Factor Erythroid 2-Related Factor 2 is Essential for Low-Normobaric Oxygen Treatment-Mediated Blood-Brain Barrier Protection Following Ischemic Stroke - Xiao-Xiao Ma; Hai-Yi Xie; Pin-Pin Hou; Xiao-Jing Wang; Wei Zhou; Zhen-Hong Wang (Molecular Neurobiology, 2024)

Economical-effective purification of brackish water through an integrated capacitive desalination & boron adsorption system - Liping Yang; Yixiang Li; Lu Guo; Pin Ma; Zhi Yi Leong; Jing Wang; Hui Ying Yang (Desalination, 2024)

Cationic segregation of Ca2Mn3O8 enabling high selectivity for fluoride ions through capacitive deionization - Wei Wang; Pin Ma; Haibo Li (Desalination, 2023)

Arginase from Priestia megaterium and the Effects of CMCS Conjugation on Its Enzymological Properties - Yu Liang Jiao; Pin Quan Shen; Shu Fang Wang; Jing Chen; Xiang Hong Zhou; Gui Zhen Ma (Current Microbiology, 2023)

Rational targeting of autophagy in colorectal cancer therapy: From molecular interactions to pharmacological compounds - Canhui Jin; Tianbao Wang; Yanhui Yang; Pin Zhou; Juncheng Li; Wenhao Wu; Xin Lv; Guoqing Ma; Aihong Wang (Environmental Research, 2023)

The Effect of Microplastics-Plants on the Bioavailability of Copper and Zinc in the Soil of a Sewage Irrigation Area - XinYue Ma; XiaoLi Ma; Pin Chen (Bulletin of Environmental Contamination and Toxicology, 2023)

Correction to: Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Acute temperature changes induce an oxidative stress response in kidney cells of grass carp Ctenopharyngodon idellus - Pin Ma; Xiaoyan Yin; Dapeng Li; Li Li; Rong Tang (Fisheries Science, 2021)

Dietary selenium promotes the growth performance through growth hormone–insulin-like growth factor and hypothalamic–pituitary–thyroid axes in grass carp (Ctenopharyngodon idella) - Pin Ma; Zhenyi Hu; Li Li; Dapeng Li; Rong Tang (Fish Physiology and Biochemistry, 2021)

Advances in intervention methods and brain protection mechanisms of in situ and remote ischemic postconditioning - Chun-Yan Li; Wei Ma; Kuang-Pin Liu; Jin-Wei Yang; Xian-Bin Wang; Zhen Wu; Tong Zhang; Jia-Wei Wang; Wei Liu; Jie Liu; Yu Liang; Xing-Kui Zhang; et al. (Metabolic Brain Disease, 2021)

Optimization of the protoplast transient expression system for gene functional studies in strawberry (Fragaria vesca) - Yi-Jie Gou; Yu-Lian Li; Pin-Pin Bi; Dan-Juan Wang; Yang-Yang Ma; Yang Hu; Hou-Cheng Zhou; Ying-Qiang Wen; Jia-Yue Feng (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Detection of thermal pollution from power plants on China’s eastern coast using remote sensing data - Pin Ma; Xiaoyan Dai; Zhongyang Guo; Chao Wei; Weichun Ma (Stochastic Environmental Research and Risk Assessment, 2017)

Characterization of extracellular polymeric substances in biofilms under long-term exposure to ciprofloxacin antibiotic using fluorescence excitation-emission matrix and parallel factor analysis - Chaochao Gu; Pin Gao; Fan Yang; Dongxuan An; Mariya Munir; Hanzhong Jia; Gang Xue; Chunyan Ma (Environmental Science and Pollution Research, 2017)

Therapeutic value of nerve growth factor in promoting neural stem cell survival and differentiation and protecting against neuronal hearing loss - Zhao Han; Cong-Pin Wang; Ning Cong; Yu-Yan Gu; Rui Ma; Fang-Lu Chi (Molecular and Cellular Biochemistry, 2017)

Predictive value of circulating miR-328 and miR-134 for acute myocardial infarction - Fucheng He; Pin Lv; Xue Zhao; Xi Wang; Xuehan Ma; Weiwei Meng; Xianchun Meng; Shuling Dong (Molecular and Cellular Biochemistry, 2014)

Stoichiometric shifts in surface soils over broad geographical scales: evidence from C hina's grasslands - Yuanhe Yang; Jingyun Fang; Chengjun Ji; Arindam Datta; Pin Li; Wenhong Ma; Anwar Mohammat; Haihua Shen; Huifeng Hu; Benjamin O. Knapp; Pete Smith (Global Ecology and Biogeography, 2014)
Aim The identification of stoichiometric flexibility is crucial for understanding carbon–nitrogen–phosphorus ( C – N – P ) interactions and ecosystem dynamics under a changing environment. However, current evidence of stoichiometric flexibility mainly comes from manipulation experiments, with little evidence from large‐scale observations. Location Alpine and temperate grasslands across northern C hina. Methods Using soil profiles derived from a historical national soil inventory and a contemporary regional soil survey across C hina's grasslands, we examined temporal changes in topsoil C : N : P ratios over recent decades. Results Topsoil C:N ratios of five major grassland types exhibited some flexibility but did not show significant changes over the sampling interval. Non‐significant changes in topsoil C : N ratios were observed both in alpine grasslands on the T ibetan P lateau and in temperate grasslands on the Inner Mongolian Plateau. Consistent with the relatively stable C : N ratios, the slope of the soil C – N stoichiometric relationship did not differ significantly between the two sampling periods. Soil N:P ratios in the surface layer increased significantly over the sampling interval, however, with an overall increase of 0.60 (95% confidence interval 0.58–0.62). A larger increase in soil N : P ratio was found in temperate grasslands on the I nner M ongolian P lateau than in alpine grasslands on the T ibetan P lateau. Moreover, the slope of the soil N – P stoichiometric relationship in these grassland ecosystems became steeper over the sampling interval. Main conclusions These results demonstrate the stability of topsoil C : N stoichiometry but variability in N : P stoichiometry over broad geographical scales, highlighting that soil C and N are tightly coupled, but N and P tend to be decoupled under a changing environment.

Increased topsoil carbon stock across China's forests - Yuanhe Yang; Pin Li; Jinzhi Ding; Xia Zhao; Wenhong Ma; Chengjun Ji; Jingyun Fang (Global Change Biology, 2014)
Biomass carbon accumulation in forest ecosystems is a widespread phenomenon at both regional and global scales. However, as coupled carbon–climate models predicted, a positive feedback could be triggered if accelerated soil carbon decomposition offsets enhanced vegetation growth under a warming climate. It is thus crucial to reveal whether and how soil carbon stock in forest ecosystems has changed over recent decades. However, large‐scale changes in soil carbon stock across forest ecosystems have not yet been carefully examined at both regional and global scales, which have been widely perceived as a big bottleneck in untangling carbon–climate feedback. Using newly developed database and sophisticated data mining approach, here we evaluated temporal changes in topsoil carbon stock across major forest ecosystem in China and analysed potential drivers in soil carbon dynamics over broad geographical scale. Our results indicated that topsoil carbon stock increased significantly within all of five major forest types during the period of 1980s–2000s, with an overall rate of 20.0 g C m −2 yr −1 (95% confidence interval, 14.1–25.5). The magnitude of soil carbon accumulation across coniferous forests and coniferous/broadleaved mixed forests exhibited meaningful increases with both mean annual temperature and precipitation. Moreover, soil carbon dynamics across these forest ecosystems were positively associated with clay content, with a larger amount of SOC accumulation occurring in fine‐textured soils. In contrast, changes in soil carbon stock across broadleaved forests were insensitive to either climatic or edaphic variables. Overall, these results suggest that soil carbon accumulation does not counteract vegetation carbon sequestration across China's forest ecosystems. The combination of soil carbon accumulation and vegetation carbon sequestration triggers a negative feedback to climate warming, rather than a positive feedback predicted by coupled carbon–climate models.

Feather Keratin Deposits as Biosorbent for the Removal of Methylene Blue from Aqueous Solution: Equilibrium, Kinetics, and Thermodynamics Studies - Pin Gao; Kanzhu Li; Zhenhong Liu; Baojiang Liu; Chunyan Ma; Gang Xue; Meihua Zhou (Water, Air, & Soil Pollution, 2014)

Differential global genomic changes in rice root in response to low-, middle-, and high-osmotic stresses - Ting-chen Ma; Rong-jun Chen; Rong-rong Yu; Han-lai Zeng; Duan-pin Zhang (Acta Physiologiae Plantarum, 2009)